ANALISIS FAKTOR KEBERHASILAN UMKM AYAM GEPREK DALAM MENARIK KONSUMEN DI ERA PERSAINGAN BISNIS: STUDI KASUS AYAM GEPREK BU NOVI - Hutabarat, Siti Lutfia; Oktavia Sufa, Amanda; Sari Siregar, Efrida Rahma; Dirgantara, M. Riyan; Hayati, Fitri (LP2M Universitas Bina Bangsa, 2025)
MSMEs play a very important role in the national economy, including by creating jobs, increasing people's incomes, and encouraging local innovation. One of the MSME sectors that has great potential is culinary, because food and beverages are basic needs that are always sought after by the community. Geprek chicken is one of the most popular culinary, which is also followed by many other business actors, thus creating fierce competition between geprek chicken sellers. One of the businesses that succeeded in competing was Ayam Geprek Bu Novi, which is located around the University of Muhammadiyah North Sumatra Campus. Even though there are many competitors around him, Ayam Geprek Bu Novi still consistently gains profits. This study aims to analyze the factors that support the success of Ayam Geprek Bu Novi MSMEs in attracting consumers in the midst of fierce business competition. The research method used is qualitative with an interview approach, which involves business owners and consumers as the main informants. The data obtained is then analyzed to identify marketing strategies, competitive advantages, as well as factors that influence consumer decisions. The results of the study show that the factors that contribute to the success of Ayam Geprek Bu Novi include superior product quality with real chili chili sauce, strategic location near campus and boarding area, affordable prices, and friendly and fast service. In addition, the diversity of menus offered and digital promotions through food delivery platforms also play an important role in attracting customers.